2020
DOI: 10.1186/s12936-020-3110-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of a highly-sensitive rapid diagnostic test to screen for malaria in pregnancy in Indonesia

Abstract: Background: The sensitivity of rapid diagnostic tests (RDTs) for malaria is inadequate for detecting low-density, often asymptomatic infections, such as those that can occur when screening pregnant women for malaria. The performance of the Alere ™ Ultra-sensitive Malaria Ag Plasmodium falciparum RDT (uRDT) was assessed retrospectively in pregnant women in Indonesia. Methods:The diagnostic performance of the uRDT and the CareStart ™ Malaria HRP2/pLDH VOM (Plasmodium vivax, Plasmodium ovale and Plasmodium malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
2
29
2
Order By: Relevance
“…LAMP has shown to greatly improve the detection of these low-density infections in maternal peripheral blood during pregnancy [ 70 , 73 , 74 , 75 , 76 , 77 ] as well as in placental blood at delivery [ 77 , 78 , 79 ], when compared to microscopy, and conventional or highly sensitive RDTs ( Table 4 ). The fact that antenatal care is usually provided in clinics where the basic laboratory procedures can easily be conducted, together with the improved sensitivity for the diagnosis of gestational and placental malaria [ 70 , 74 , 75 , 77 ], suggests that LAMP could provide a valuable tool in the screening of malaria during antenatal visits or at delivery.…”
Section: Lamp For Malaria Screening In Pregnancymentioning
confidence: 99%
“…LAMP has shown to greatly improve the detection of these low-density infections in maternal peripheral blood during pregnancy [ 70 , 73 , 74 , 75 , 76 , 77 ] as well as in placental blood at delivery [ 77 , 78 , 79 ], when compared to microscopy, and conventional or highly sensitive RDTs ( Table 4 ). The fact that antenatal care is usually provided in clinics where the basic laboratory procedures can easily be conducted, together with the improved sensitivity for the diagnosis of gestational and placental malaria [ 70 , 74 , 75 , 77 ], suggests that LAMP could provide a valuable tool in the screening of malaria during antenatal visits or at delivery.…”
Section: Lamp For Malaria Screening In Pregnancymentioning
confidence: 99%
“…A previous study in pregnant women from a moderate malaria transmission site in Colombia identified a slightly higher sensitivity of the UsmRDT over the standard RDT (85.7% versus 82.8%), but similar specificity (> 99.0%) [ 23 ]. Using archived blood samples from pregnant women from a low transmission setting in Indonesia, a study reported no difference in performance of the UsmRDT relative to the standard CareStart combo-RDT kit [ 24 ]. These contrasting reports present the need to provide more evidence on the performance of the UsmRDT against standard malaria RDT kits to influence policies relating to malaria diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these results raise the question of the added value of the uRDTs evaluated in this study, in Mozambique. In fact, the utility of these uRDTs remains unclear, partly as a result of the emergent body of evidence in line with the performance outcomes presented here [21,26,27,29]. In summary, three main use-cases have been proposed for this diagnostic tool: (1) To be used in malaria elimination contexts to more accurately measure prevalence or guide test-and-treat strategies to interrupt malaria transmission in the community, (2) for improved case management, and 3) to detect low-density infections among pregnant women.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, studies conducted among pregnant women observed a higher performance of uRDTs among afebrile women compared to febrile ones [28,30]. These studies were conducted under laboratory conditions using retrospectively collected samples [28][29][30]. However, there is currently no evidence of the performance of uRDTs among pregnant women when the tests are directly conducted at point of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation